NANOSIZED MATERIALS FOR CREATION OF HIGH SENSITIVE SEMICONDUCTOR GAS SENSORS: DOI: https://doi.org/10.17721/1728-2209.2023.1(58).10 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2023)
Background. The development of new oxide nanosized materials based on tin dioxide is extremely relevant for creation of adsorption-semiconductor gas sensors that have high sensitivity and good dynamic characteristics in combination with small mass, dimensions and low energy consumption. An increase in the sensitivities of the semiconductor sensors based on tin dioxide can be achieved, in particular, by reducing the sizes of the particles of the semiconductor materials, which leads to an increase in the proportion of atoms of the material on its surface in relation to the total number of atoms in the volume, which can determine the size effect in the formation of the sensitivities of the sensors.Methods. The physico-chemical properties of the synthesized materials were studied using TEM, XRF, IR spectroscopy, DTA-DTG, argon thermal desorption and electrophysical method.Results. Nanosized initial semiconductor tin dioxide based sensor material has been synthesized by sol-gel technique and characterized by XRD, IR-spectroscopy, DTA-DTG and TEM-methods. Nanosized SnO2-based sensor materials have been prepared from the pastes with different quantities of tin dioxide and carboxymethylcellulose and formatted at various temperatures 400 and 600 oC. It is found that the composition of the pastes significantly affects the characteristics of the sensors obtained on their base. The sensors created on the paste with 70 % SnO2 have the higher sensitivities to hydrogen.The characteristics of the sensors of different compositions are explained by necessity of the presence of a sufficient number of contacts between the particles of the sensor material, which ensure the electrical conductivity of the sensor. Extreme nature of the temperature dependences of the sensitivities of the sensors based on the synthesized materials confirms the contribution of the size effect in the formation of the sensitivity.Conclusions. High sensitive semiconductor sensors to hydrogen were created on the base of nanomaterial synthesized by a zol-gel method. Study of the gas-sensitive properties of hydrogen sensors created on the basis of the synthesized nanomaterial have shown the prospects of using it to create highly sensitive semiconductor gas sensors.
Keywords: nanosized materials, sol-gel synthesis, tin dioxide, semiconductor sensors, sensitivity to hydrogen.